ARABIC LEARNING PARADIGM IN STRENGTHENING THE QUR’ANIC STUDIES AT PTKIN IN SOUTH SULAWESI: MUHAMMAD ARKOUN'S SEMIOTIST CRITICAL PERSPECTIVE - Muhammad Rusydi; Suhadi Suhadi (Al-Qalam, 2022)
This research article focuses on analyzing the Arabic learning paradigm in strengthening the Qur'anic studies through Muhammad Arkoun's semiotist critical study. This research is a descriptive qualitative research using in-depth interviews, participatory observation, documentation, and reference tracing as the collection method. The collected data is then processed through 1) editing, 2), classifying, 3) analyzing, 4) and concluding. The results showed that Arabic learning paradigm in strengthening the Qur’anic studies at PTKIN in South Sulawesi showed that the Arabic learning has quite varied study dynamics so that it indicated that the study of Arabic was already running on the correct paradigm. In general, it can be said that there are two types of Arabic learning applied, which in this case is Arabic as MKDU,  General Basic Course, with an orientation on Ta'lim al-Lugah al-Arabiyah li al-Agradh al-Khassah and Arabic learning in various special programs like intensive Arabic learning, whether based on ma'had al-jamiah or not. In the process, the learning process cannot be separated from the Arabic learning, both of which are taught in an interdisciplinary study cycle. The construct of Arabic learning paradigm in strengthening the Qur'anic studies at PTKIN in South Sulawesi through Muhammad Arkoun's semiotist critical perspective refers to three levels of Qur’anic studies by making Arabic as one of the objects of study which in this case is the historical-anthropological level, linguistic-semiotic level, and theological-religious level. In the process, the Arabic learning is used as a forum to accommodate various practical-methodical frameworks of the interpretation of the Qur'an considering the position of Arabic in this context as the language of the Qur'an. A more contextual and historical understanding of the Qur'an can only be realized when the Arabic with its various historical dimensions as summarized in the various scientific frame that build it is also studied comprehensively and holistically.